Political ecology for civil society - Beltrán, María J. (2015)
A manual product of the ENTITLE project designed for the use of civil society organisations and active citizens. The book offers an accessible insight into political ecology issues and provides intellectual and practical tools based from the experiences of the new generation of political ecologists trained within the project. Organized around the 5 main themes of the ENTITLE project: environmental conflicts, disaster capitalism, social movements, commons, and democracy, the book explains what is the contribution of a political ecology approach, defines key concepts and illustrates theories, methods and tools through a case studies' approach so to provide readers with accessible and transferable knowledge. The manual also seeks to reflect on how different scholars have defined this scholar-activist relation and to enhance collaborations between civil society and academia for the purpose of transforming current unjust and unsustainable social ecological arrangements.